Wavering Sonorities and the Nascent Film Noir Musical Style - Hickman, Roger (Journal of Film Music, 2010)
Film noir emerged in the early 1940s and remained a potent force in Hollywood filmmaking for nearly two decades. In the groundbreaking article “Notes on Film Noir,” Paul Schrader observes, “Most every dramatic Hollywood film from 1941 to 1953 contains some noir elements.”1 Because of this pervasive influence, film noir has received extensive coverage in both scholarly and popular press. Yet a precise definition of the movement is elusive. Cinema studies offers no consensus as to whether film noir is a genre or just a style, what the defining characteristics are, when the movement began, and which films should be included in its canon. The situation remains much as Schrader described in 1972, “Almost every critic has his own definition of film noir.”2 Unfortunately, most of these definitions do not consider music. Relatively little has been written about music for film noir. Cinema scholars have concentrated on its visual and dramatic qualities,3 and musical scholars have treated the topic within larger contexts or have focused on the singular aspect of jazz.4 Further research into the music of film noir bears significance both to cinema studies, where it can clarify further the notion of “noirness,” and to musicology, where it can illuminate the expanding roles of both popular and modern musical styles in Hollywood films during the 1940s and 50s.